Moving in the right direction in the discussion section of research articles - Al-Shujairi, Yasir Bdaiwi Jasim; Tan, Helen; Abdullah, Ain Nadzimah; Nimehchisalem, Vahid; Lee, Geok Imm (Universiti Putra Malaysia Press, 2019)
The discussion section forms an integral part in the writing process of a research article (RA). It is a pivotal section where proposition of findings and rebuttal of claims conflate. For such writing to be credible and be accepted by the discourse community, it is important for writers to structure their arguments along the accepted communicative moves. To date, a plethora of studies on rhetorical moves in research articles abounds but most research focuses on only moves which are at the macro level. Therefore, this paper seeks to examine not only the rhetorical moves but also the relevant steps within a move. The study also examined the linguistic realizations that identify each move and step. To realize the objectives, a qualitative analysis of 16 discussion sections of RAs in medical sciences and applied linguistics disciplines were conducted. A model of 8 moves was used as an initial framework for move analysis. The findings demonstrate the manifestation of three steps in move 1 and another three in Move 5. In addition, two moves namely Implications and Summary of Results were also found in the analysis. Regarding the disciplinary differences, move 2 (Finding) and move 5 (Explanation) were found to be obligatory in AL discipline while Move 7 (Concluding information) was the only obligatory move in MS discipline. Based on the findings, a more holistic model on moves and steps was drawn along with a list of linguistics cues pertinent in each move and step.